Desarrollo de prácticas de automatización a través de un módulo didáctico con el plc s7-1200 para la clasificación de piezas en bandas transportadoras - Baque Bonilla, Oscar Eduardo (2017)
The objective of designing and implementing the module for the part classification process controlled by a PLC (Programmable Logic Controller) Siemens S7-1200 is that the students of the Electromechanical Engineering major of the Technical University of Cotopaxi have a tool where they can develop their practices in an appropriate way. By means of the deductive method allowed to realize the assembly, configuration and programming of the devices and therefore the total operation of the process. The materials used were aluminum profiled for the support structure, where the sensors were located: inductive, reflective, optical fiber, magnetic end of stroke, positioning encoder of conveyor belt 48.5cm long x 4cm wide, cylinders linear pneumatics activated by solenoid valves, relays for the activation of the 24VDC motor, the process control was carried out using a PLC, monitored from an HMI (Human Machine Interface) developed in a computer using the LabVIEW software and an OPC server KEP server. Through the 100 performance tests carried out, with their respective parts, 95% of correctly classified parts and 5% of incorrectly classified parts were obtained, which was modified until 100% of correctly classified parts were obtained. We conclude that by implementing the parts classification system using electrical, mechanical and pneumatic systems, students will be able to practice and thus become familiar with real industrial processes to establish solutions to possible problems of automation. We recommend that the user manual and respective technical data of each of the module components be reviewed before the module is put into operation.